On Competition between Javan Rhino (Rhinoceros Sondaicus) and Javan Bull (Bos Javanicus) at Ujung Kulon National Park with Allee Effect - Eric Harjanto; Respati Mentari (Communication in Biomathematical Sciences, 2019)
In the last few decades, it has been reported that the population of Rhino (Rhinoceros Sondaicus) at the Ujung Kulon National Park has been reaching a stagnation at the number 50s, despite the existing territory can support a much larger number of Rhinos. Here, we construct a dynamical model representing the interaction between Rhino and Bull (Bos Javanicus) with Allee effect for the Javan rhinos population. This Allee effect may occur in the field, among others, due to the solitary behaviour of Rhino within large territory, imbalance of age structure and gender and difficulty of finding mates in Javan rhinos population which causes inbreeding in the population. In this paper, we follow the previous paper on the territorial competition between Javan  rhino and Javan bull at Ujung Kulon National Park and add Allee effect factor on the Javan rhino's population. We give a proof on the boundedness of the solution and explanation on the bifurcations that occur in the model. One of these bifurcations plays an important role in the system. Some simulations and suggestion on how to improve the survival of Javan rhino is also included.